‘Eyn Mercklich Underscheyd’: Catholic Reactions to Luther’s Doctrine of the Priesthood of all Believers, 1520–25 - Bagchi, David (Studies in church history, 1989)
After the great Reformation principles of ‘faith alone’ and ‘Scripture alone’, probably the most revolutionary doctrine commonly associated with Martin Luther is that of the priesthood of all believers. It is well known that, as it appears in his address ‘to the Christian nobility of the German nation’ of 1520, he intended this doctrine to bring down the walls of the new Jericho by striking at the heart of the distinction between clergy and laity on which the medieval Church was based. What is less well known is the reaction to this doctrine of Luther’s contemporaries, and in particular his critics. I propose to look at how they regarded the reformer’s conception of the universal priesthood, and what they thought its implications were, in the hope of shedding more light on its contemporary significance.